Senhora, de José de Alencar: do folhetim ao romance - Cruz, Catarina Reis Matos da (2010)
This dissertation aims to develop an interpretative analytical study of the novel, Senhora , novelist José de Alencar in confrontation with the feuilleton, journalistic genre of 19th century. The central aim is to verify the presence of the characteristics of the feuilleton composition in novel Senhora , realizing that the writer began his literary career with journalism experience. The themes are: Chapter I presents the landscape of the feuilleton genre until the formation of novel. Chapter II deals with the storytelling feuilleton process and novel Senhora in parallel, by means of the likelihood. Chapter III shows us the fictional romance and society from Rio de Janeiro in middle of nineteenth century in approximation and detachment from the romance-feuilleton. The theoretical support parameters are: Marlyse Meyer (1996), Ribeiro (1996), Roberto Schwartz (2000), Tzvetan Todorov (2008), Antonio Candido (1982), (1975) and (2007) Mikhail Bakhtin (1993) and (2003), among others. We priorized the method of hypothetical-deductive approach because search assumes that Alencar would have used the methodology and procedures feuilleton narrative structural (romance-feuilleton) in Senhora novel. The procedures of analysis and synthesis are constants in the interpretation of the novel, resulting in a search descriptive self-explanatory, between the romance-feuilleton and Senhora novel and similar structures of both